Impact of Staphylococcus aureus phenotype and genotype on the clinical characteristics and outcome of infective endocarditis. A multicentre, longitudinal, prospective, observational study. (September 2018) - Fernández-Hidalgo, N.; Ribera, A.; Larrosa, M.N.; Viedma, E.; Origüen, J.; de Alarcón, A.; Fariñas, M.C.; Sáez, C.; Peña, C.; Múñez, E.; García López, M.V.; Gavaldà, J.; et al.
Abstract: Objective: We aimed to evaluate the impact of Staphylococcus aureus phenotype (vancomycin MIC) and genotype ( agr group, clonal complex CC) on the prognosis and clinical characteristics of infective endocarditis (IE). Methods: We performed a multicentre, longitudinal, prospective, observational study (June 2013 to March 2016) in 15 Spanish hospitals. Two hundred and thirteen consecutive adults (≥18 years) with a definite diagnosis of S. aureus IE were included. Primary outcome was death during hospital stay. Main secondary end points were persistent bacteraemia, sepsis/septic shock, peripheral embolism and osteoarticular involvement. Results: Overall in-hospital mortality was 37% ( n  = 72). Independent risk factors for death were age-adjusted Charlson co-morbidity index (OR 1.20; 95% CI 1.08–1.34), congestive heart failure (OR 3.60; 95% CI 1.72–7.50), symptomatic central nervous system complication (OR 3.17; 95% CI 1.41–7.11) and severe sepsis/septic shock (OR 4.41; 95% CI 2.18–8.96). In the subgroup of methicillin-susceptible S. aureus IE ( n  = 173), independent risk factors for death were the age-adjusted Charlson co-morbidity index (OR 1.17; 95% CI 1.03–1.31), congestive heart failure (OR 3.39; 95% CI 1.51–7.64), new conduction abnormality (OR 4.42; 95% CI 1.27–15.34), severe sepsis/septic shock (OR 5.76; 95% CI 2.57–12.89) and agr group III (OR 0.27; 0.10–0.75). Vancomycin MIC ≥1.5 mg/L was not independently associated with death during hospital nor was it related to secondary end points. No other genotype variables were independently associated with in-hospital death. Conclusions: This is the first prospective study to assess the impact of S. aureus phenotype and genotype. Phenotype and genotype provided no additional predictive value beyond conventional clinical characteristics. No evidence was found to justify therapeutic decisions based on vancomycin MIC for either methicillin-resistant or methicillin-susceptible S. aureus .